RELEVANCE OF ABDURRAHMAN WAHID'S (GUS DUR) PLURALISM THOUGHT AS A STRENGTHENING OF RELIGIOUS MODERATION IN GENERATION Z - Sultan Fattahillah Puara; Mahmud Muhsinin; Mukayat Al Amin (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
This study aims to analyse the relevance of pluralist thought pioneered by Abdurrahman Wahid (Gus Dur) to Generation Z as a means of strengthening religious moderation in the current era, enabling them to act wisely in various situations and phenomena. This research employs a library research method, involving the collection of written data or works related to Gus Dur’s pluralist ideas, which are bibliographical in nature. The findings of this study indicate that Gus Dur’s pluralist thought remains highly relevant to the challenges faced by Generation Z today. The discussion identifies religious moderation from the perspective of Gus Dur’s pluralism, encouraging imitation and emulation of his attitudes and behaviours when addressing various religious situations and phenomena. Gus Dur serves as a role model for demonstrating tolerance, inclusivity, and harmony within diversity—qualities that are crucial for Generation Z, who navigate a world of digital information and complex social dynamics. This study concludes that Gus Dur’s pluralist views significantly contribute to strengthening religious moderation among Generation Z, fostering a spirit of tolerance and inclusiveness, and reinforcing national solidarity and unity. For future researchers, it is recommended to further develop similar studies to provide deeper, more comprehensive insights and address existing research gaps.